Ina Nara Amayali sebagai Representasi Kultural: Analisis Simbolisme dan Struktur Sosial dalam Ritual Perkawinan Tradisional Masyarakat Adat Wetang - Letlora, Yohanes Andrias; Rumra, Fatmawati; Bandjar, Antasari (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
This study aims to examine, analyze, and describe the symbolism and meanings embedded in the Ina Nara Amayali tradition—a customary marriage ritual practiced by the indigenous community of Wetang Island—as a cultural representation rich in social values. Employing a qualitative approach, the research utilizes methods of observation, in-depth interviews, and documentation. The study was purposively conducted in the Wetang Island District, involving key informants such as customary leaders and indigenous community members with deep knowledge of the ritual practices. The findings reveal that Ina Nara Amayali is not merely a matrimonial ceremony but a social structure that governs interactions among extended families and the indigenous community through culturally meaningful symbols. Elements such as red sopi (traditional liquor), two pigs, emas bulan and emas babi (gold items), basta cloth, and lakpona serve not only as ritual components but also as representations of ethical and moral values that shape communal social behavior. The gathering of both families, accompanied by customary figures like Sniri/Mataruma and the customary chief, highlights the embedded social order within the ritual tradition. This study offers new insights into how symbols in local cultures not only represent identity but also function as social binding mechanisms that reinforce communal harmony. The research recommends the preservation of local traditions as vital sources of social knowledge and cultural wisdom, contributing to the advancement of social sciences and humanities, particularly in understanding the relationship between cultural symbolism and the social structures of indigenous island communities.